Oxidative Burst with Dihydrorhodamine Test: Reference Values in Healthy Controls - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; ÖĞÜLÜR, İSMAİL; BARIŞ, SAFA (TURKISH SOC IMMUNOLOGY, 2015)
Objectives: In this study, we report reference data of stimulation index (SI) and variation coefficient (VC) data in dihydrorhodamine test in healthy controls. Materials and methods: Two hundred ten healthy controls without primary immunodeficiency warning signs and chronic disease were enrolled in this study. Evaluation was performed in 184 individuals (67 females, 117 males; mean age 9.0 +/- 9.6 years; range 0.3 to 59.2 years) with full data analysis. 2 mL peripheral blood samples were taken from healthy controls and lysis of erythrocytes was provided in flow cytometer tubes. The cells were washed twice with Hank's buffered salt solution (HBSS) and incubated at 37 degrees C for 14 minutes in the 50 ng/mL phorbol myristate acetate (PMA) stimulation. The cells were immediately evaluated using gating granulocytes in the BD FACS Calibur flow cytometer tool. The SI was calculated by dividing the ratio of geometric mean of fluorescence intensities obtained from PMA stimulated neutrophils to non-stimulated values. In flow cytometry, VC values of fluorescence intensity on the x-axis of histogram were obtained in PMA stimulated cells. Results: In the healthy controls, SI values were observed to vary ranging between 20.1 and 125.2 (mean 36.75 +/- 18.3). In the same series, VC values were between 9.9-25.2 (mean 18.2 +/- 3.7). Conclusion: Besides the use of a diagnostic test for chronic granulomatous disease, DHR test is useful in identifying the inheritance type of this disease and carriers. Values presented herein can be used as reference data for the assessment of patients and carriers.
Keywords: Chronic granulomatous disease; dihydrorhodamin; oxidative burst; CHRONIC GRANULOMATOUS-DISEASE; OXIDASE